ANALISIS PELANGGARAN PERJANJIAN KERJA WAKTU TERTENTU PADA TENAGA KERJA ASING TERHADAP UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN DALAM PUTUSAN MAHKAMAH AGUNG TINGKAT KASASI NOMOR: 286/K/Pdt.Sus-PHI/2013 - Gladys Virginia Sumito; Andari Yurikosari (Fakultas Hukum Universitas Tarumanagara, 2018)
Law number 13 of 2003 concerning employment along with the implementation and not only regulating the use of Indonesian workersarrangements not only regulating the use of Indonesian not not only regulating the use of Indonesian workers, but also regulates the use of foreign workers. as stipulated in articles 42 to article 49 of law 13 of 2003 concerning employment. The working relationship between employers or employers and TKA is based on PKWT and for the sake of law it cannot become PKWTT, but in practice there are still many employers or employers who often misuse TKA to work in Indonesia continuously, so the main goal is to hire TKA which is basically the transfer of knowledge and technology cannot be carried out properly. And the main principle of hiring TKA is that it can only be employed in Indonesia in employment relations for certain positions and a certain time is not reached. Unfortunately, until now there have been no sanctions that can burden the employers or employers if they violate the PKWT so that the deviations from the provisions governing the use of foreign workers to date are still prevalent in Indonesia.